Effectiveness Of Powerpoint-Assisted Discovery Learning Model On Critical Thinking Abilities In Elementary School Mathematics - Hayuningtyas, Prestanti; Riyadi, Slamet; Atmojo, Idam Ragil Widianto (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to determine the effectiveness of learning models assisted by power point media on the critical thinking skills of mathematics elementary school students. The writing of this research uses qualitative research methods, with a descriptive approach, where the basis of the discussion takes the results of literature studies, through several sources from books and relevant scientific articles and journals from previous research results that are in accordance with the topic of discussion. Based on the results of this study, it is found that the discovery learning learning model assisted by power point media has effectiveness on the critical thinking ability of elementary school students' mathematics. By using the discovery learning model assisted by power point media, students become easier to understand learning materials visually and are active and creative during learning activities. By applying the discovery learning method assisted by power point media at the elementary level, it is hoped that it can improve the quality of learning, and students can better understand a concept from learning.